THE EFFECTS OF WEIGHT LOSS AND AEROBIC EXERCISE ON 10-YEAR AND LIFETIME ASCVD RISK CALCULATED USING THE POOLED COHORT EQUATIONS - Brown, Tyler (East Carolina University, 2022)
BACKGROUND: Atherosclerotic Cardiovascular Disease (ASCVD) is the leading cause of morbidity and mortality in the United States. The American Heart Association (AHA) and American College of Cardiology (ACC) developed the Pooled Cohort Equations (PCE) to estimate10-year and lifetime ASCVD risk. Exercise and hypocaloric diets reduce ASCVD risk scores by decreasing blood pressure and cholesterol. However, there are currently no data on the magnitude of change in ASCVD score from a lifestyle intervention. METHODS: twenty-four overweight and obese adults (Age: 46.5 ± 10.5 yrs.; Weight: 95.5 ± 12.7 kg; BMI: 34.4 ± 3.4 kg/m2) participated in 10 weeks of supervised aerobic exercise while participating in an OPTIFAST weight loss program to achieve clinically significant weight loss ([greater-than-or-equal-to]7% body weight). Body composition was measured using a whole-body DEXA scan. Cardiorespiratory fitness was measured using the modified balke protocol. The OPTIFAST program was ~800 kcals per day of total meal replacement consumed as shakes, bars, and soups. By week 8, participants increased their daily intake to 1300-1500 kcals and could replace two products with whole foods per day. Participants were also encouraged to attend weekly behavioral classes to assist with dietary compliance. The weekly aerobic exercise volume began at 300 MET min per week and increased by 50 MET min each week until 700 MET min each week was reached. 10-year and lifetime ASCVD risk scores were calculated using the PCE. RESULTS: At baseline, participants had a mean 10-year ASCVD risk of 3.0% and a mean lifetime risk of 32.8%. Following the intervention, there was a mean decrease in body weight ( -8.4 kg, -9.9 %, p<0.001), systolic BP ( -9.1 mmHg, p<0.001), diastolic BP ( -5.7 mmHg, p<0.001), total cholesterol ( -15.1 mg/dL, p<0.001), low-density lipoproteins ( -7.8 mg/dL, p<0.006), and high-density lipoproteins ( -2.4 mg/dL, p<0.038). There were also reductions in 10-year ( -0.6%, p<0.001) and lifetime ASCVD risk ( -8.1%, p<0.006) after the intervention. Changes in ASCVD risk were associated with changes in systolic BP (r=0.481, p<0.017) and diastolic BP (r=0.64, p<0.001), but not lipid values. No associations were observed between the change in 10-year or lifetime ASCVD risk in body composition or fitness variables. CONCLUSION: Our results suggest a combined weight loss and aerobic exercise program elicited a large change in lifetime scores, but not in 10-year ASCVD scores. Future research should investigate the impact of lifestyle interventions on participants in populations with high ASCVD risk at baseline.
Keywords: ASCVD Risk; Weight loss and Exercise; Lifestyle Intervention; Cardiovascular system--Diseases--United States--Prevention; Atherosclerotic plaque--Prevention; Exercise tests; Health behavior